Radar plots facilitate differential diagnosis of acute promyelocytic leukemia and NPM1+ acute myeloid leukemia by flow cytometry. Issue 4 (10th December 2020) - Gupta, Monali; Jafari, Katayoon; Rajab, Amr; Wei, Cuihong; Mazur, Joanna; Tierens, Anne; Hyjek, Elizabeth; Musani, Rumina; Porwit, Anna
Abstract: Background: Acute promyelocytic leukemia (APL) is one of the most life‐threatening hematological emergencies and requires a prompt correct diagnosis by cytomorphology and flow cytometry (FCM) with later confirmation by cytogenetics/molecular genetics. However, nucleophosmin 1 muted acute myeloid leukemia ( NPM1+ AML) can mimic APL, especially the hypogranular variant of APL. Our study aimed to develop a novel, Radar plot‐based FCM strategy to distinguish APLs and NPM1+ AMLs quickly and accurately. Method: Diagnostic samples from 52 APL and 32 NPM1+ AMLs patients were analyzed by a 3‐tube panel of 10‐color FCM. Radar plots combining all markers were constructed for each tube. Percentages of positive leukemic cells and mean fluorescence intensity were calculated for all the markers. Results: APL showed significantly higher expression of CD64, CD2, and CD13, whereas more leukemic cells were positive for CD11b, CD11c, CD15, CD36, and HLA‐DR in NPM1+ AMLs. Radar plots featured CD2 expression, a lack of a monocytic component, lack of expression of HLA‐DR and CD15, and a lack of a prominent CD11c+ population as recurring characteristics of APL. The presence of blasts with low SSC, presence of at least some monocytes, some expression of HLA‐DR and/or CD15, and a prominent CD11c population were recurrent characteristics of NPM1+ AMLs. Radar plot analysis could confidently separate all hypergranular APL cases from any NPM1+ AML and in 90% of cases between variant APL and blastic NPM1 + AML. Conclusion: Radar plots can potentially add to differential diagnostics as they exhibit characteristic patterns distinguishing APL and different types of NPM1+ AMLs.